Geopedology as base information to forest suitability zoning in a catchment of norwestern patagonia, argentina - Frugoni, Maria Cristina; González Musso, Romina; Falbo, Gabriel; Zapiola, Dolores (Facultad de Humanidades Universidad Nacional del Comahue, 2016)
Geopedology at a semi-detailed scale (1:50.000) was carried out in Buta Mallín catchment which includes an area of 21.065ha, in the northwest of Neuquén province, Argentine Patagonia. Geopedology provides a spatial dimension of soil-landscape relations, which are displayed in a map and its legend, showing the geoforms (contours) and their soils (content), based on the premise that soil islandscape as well as profile. According to this approach three landscapes were recognized: glacial modeled mountains, plateau and valley. The relief consists mainly of steep to very steep slopes, and valley bottoms with poorly drained soils.Lithology (parent material) corresponds to holocene volcanic ash in the western sector of the study area, while the eastern sector is dominated by tuff. Twenty terrain forms and their soils were identified. With this basic information, attribute tables were constructed considering landscape and soil properties. Regarding soils, physical fertility properties were considered, since these are the most correlated ones with Pinus ponderosa (pino ponderosa) growth, the main species used in afforestation in Patagonia. Those tables were included and analized with a GIS (Geographic Information System) to obtain a forest suitability map. The study areashows four forest suitability classes. Suitable: 37ha; moderately suitable: 4.512ha; marginally suitable: 6.072ha; not suitable: 10.444ha. The main limitations of the area are the very steep slopes, height and the areas dominated by rock outcrops and detrital covers. Nothofagus antarctica (ñire) shrubs cover part of the suitable areas; because of conservation criteria of these natural communities, these lands were considered not suitable. On the other side, there are more than 4.000 ha of moderately suitable lands, which can be considered for a more detailed study.Transhumant cattle raising is the main land use system in this catchment, which is an ancient culture of the Northern Neuquian peasants. Decision makers could boost the development of ...